Microbes Inactivation by Combination of Pulsed Electric Field and Heat Treatment on Coconut Water for Isotonic Drink - Saparianti, Ella; Harijono, Harijono; Wulandari, Budi Dwi (Jurnal Teknologi Pertanian, 2008)
Pulsed electric field is one of non-thermal food preservation method. Pulsed electric field has more advantages than thermal preservation. It can inactivate microbe without reducing flavor, taste, and nutrition, compared to traditional thermal sterilization. Coconut water contains natural electrolytes. There are some recognized benefits of coconut water, one of them is as a natural isotonic drink. The aim of this research were to understand the effectiveness of microbe inactivation with pulsed electric field with or without heat treatment on coconut water, and to understand chemical changes of this process. Experimental design used in this research was randomized block design with 2 factors. The first factor was pretreatment (heat treatment and without heat treatment) and the second factor was the magnitude of electric field which were 0.60; 0.75; 1.20, and 1.50 kV/cm). Pulsed electric field of 1.50 kV/cm without heat treatment reduced total microbes of 3 log cycles and total of E. coli of 2 log cycles. Heat treatment could reduce total microbes of 2 log cycles. Whereas pulsed electric field combined with heat treatment reduced total microbes of 5 log cycles and destroyed E. coli. Pulsed electric field with heat treatment was in microbial and E. coli inactivation than without heat treatment, but this treatment decreased sodium and potassium content of coconut water. Pulsed electric field with heat treatment produced more reducing sugar and decreased more vitamin C than without heat treatment.Key words: pulsed electric field, heat treatment, isotonic drink, coconut water